XIMIYA SABAQLARÍN INTEGRACIYALASQAN OQÍTÍW - Aytbaeva, X.B.; Aymurzaeva, L.G. (SCIENCE and SOCIETY, 2025)
This article presents the issues of integrated learning using the pinboard method when teaching chemical elements in chemistry lessons. With integrated learning, students develop interdisciplinary competence, logical thinking is formed, and creativity and activity of students increase.